Consumer attitudes toward and utilization of decision-making aids in the online environment - Karaduman, Cansu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
With the advent of the Internet, consumers started to enjoy emerging tools such as recommendation agents, virtual dressing rooms, online shopping friends or wish lists. In the past, consumers relied on friends, relatives, salespeople or publications mostly, but now they also use various online tools that help in shaping their decisions. Yet, there are some considerations that must be taken into account when evaluating the advantages or disadvantages of such tools. Online decision aids influence the purchase behavior and preferences of consumers in many ways. The objective of this thesis is to determine the basics of consumer attitudes toward and utilization of decision making aids. In this thesis, the general facets of attitudes such as trust toward web-sites, perceived usefulness, perceived ease of use, perceived cognitive effort, perceived personalization, and perceived entertainment value, demographic variables and specific tool types are elaborated. A comprehensive set of online decision-making tools is developed. Variables that may affect attitudes toward such tools are adapted from marketing literature. Usage frequencies of such tools are measured and clustering analyses have been made on the basis of utilization of online decision-making aids. Data are collected from 383 participants with the purpose of probing consumer attitudes toward and utilization of online decision aids and have been analyzed via descriptive, reliability, cluster, cross-tab, independent t-test, and ANOVA tests, in order to test fourteen hypotheses and draw conclusions therein.
Keywords: Consumer -- Attitudes -- Decision making.; Electronic commerce.